Genetic alterations crossing the borders of distinct hematopoetic lineages and solid tumors: Diagnostic challenges in the era of high-throughput sequencing in hemato-oncology. (June 2018) - Shumilov, Evgenii; Flach, Johanna; Pabst, Thomas; Fiedler, Martin; Angelillo-Scherrer, Anne; Trümper, Lorenz; Joncourt, Raphael; Kohlmann, Alexander; Bacher, Ulrike
Highlights: Multiple mutations cross the borders between different hemato-oncological entities. New difficulties for diagnostic algorithms and the interpretation of the results have arisen. Targeted therapies are being tested across the borders of different entities. Abstract: Owing to the introduction of next-generation sequencing (NGS) new challenges for diagnostic algorithms and the interpretation of the results for therapeutic decision making in hemato-oncology have arisen. Recurrent somatic mutations crossing the borders between different hematological entities and solid neoplasms have been detected. In analogy to mutant TP53, the same mutation type may occur in myeloid, B- or T-lymphatic malignancies or solid neoplasms. At the same time, a certain mutation can show different prognostic outcomes in different entities and co-existence of certain mutations may change the prognostic relevance. These insights may spark the investigation of targeted therapies with the same substances across different disease entities. This review article summarizes mutations that can emerge in different hematologic and solid malignancies and summarizes other obstacles in the era of modern molecular diagnostics, such as the phenomenon of "clonal hematopoiesis of indeterminate potential" being difficult to interpret in the individual patient.